2000
DOI: 10.1034/j.1600-0420.2000.078006710.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in Fryns syndrome

Abstract: ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“… A: Fryns et al [1979], B: Young et al [1986], C: Samueloff et al [1987], D: Moerman et al [1988], E: Ayme et al [1989], F: Bamforth et al [1989], G: Cunniff et al [1990], H: Hanssen et al [1992], I: Ficcadenti et al [1993], J: Riela et al [1995], K: Van Hove et al [1995], L: Cursiefen et al [2000], M: Ramsing et al [2000], N: Pierson et al [2002], O: Arnold et al [2003]. Two of two patients reported by Fryns et al [1979] and two of eight patients reported by Ayme et al [1989] were found with the specific eye findings listed. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… A: Fryns et al [1979], B: Young et al [1986], C: Samueloff et al [1987], D: Moerman et al [1988], E: Ayme et al [1989], F: Bamforth et al [1989], G: Cunniff et al [1990], H: Hanssen et al [1992], I: Ficcadenti et al [1993], J: Riela et al [1995], K: Van Hove et al [1995], L: Cursiefen et al [2000], M: Ramsing et al [2000], N: Pierson et al [2002], O: Arnold et al [2003]. Two of two patients reported by Fryns et al [1979] and two of eight patients reported by Ayme et al [1989] were found with the specific eye findings listed. …”
Section: Discussionmentioning
confidence: 99%
“…Although initially considered a major feature of Fryns syndrome, cloudy cornea has not been reported frequently in this syndrome. In addition to cloudy cornea, other ocular findings have been reported including hypertelorism, microphthalmia, Bowman irregularities, thickened posterior lens capsule with vacuolization of lens fibers, and retinal dysplasia with rosettes and gliosis [Cursiefen et al, 2000]. Retinal gliosis and cloudy cornea may occur in an estimated one‐fifth to one‐third of those affected with this rare often lethal disorder [Van Hove et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 52 cases had at least two or three of the diagnostic guidelines listed by Fryns in Table I [Fitch et al, 1978 (one case); Fryns et al, 1979 (two cases); Goddeeris et al, 1980 (one case); Lubinsky et al, 1983 (two cases); Meinecke and Fryns, 1985 (one case); Samueloff et al, 1987 (four cases); Moerman et al, 1988 (two cases); Aymé et al, 1989 (eight cases); Bamforth et al, 1989 (five cases); Cunniff et al, 1990 (four cases); Rodríguez Gonzalez et al, 1990 (one case); Dix et al, 1991 (one case); Kershisnik et al, 1991 (two cases); Bulas et al, 1992 (one case); Pellissier et al, 1992 (two cases); Gadow et al, 1994 (one case); Langer et al, 1994 (one case); Pinar et al, 1994 (three cases); Barthé et al, 1995 (one case); Bartsch et al, 1995 (two cases); Van Hove et al, 1995 (one case); Manouvrier‐Hanu et al, 1996 (one case); Fryns and Moerman, 1998 (one case); Cursiefen et al, 2000 (one case); Vargas et al, 2000 (two cases); Davis and Samarakkody, 2002 (one case)]. We determined the frequencies of the phenotypic features found in these cases [Tables II–XIII].…”
Section: Methodsmentioning
confidence: 99%
“… In addition to patients with a CVM reported on Tables II and III, patients without a CVM were reviewed [Goddeeris et al, 1980; Lubinsky et al, 1983; Meinecke and Fryns, 1985; Young et al, 1986; Samueloff et al, 1987; Willems et al, 1991; Hansen et al, 1992; Di Meglio et al, 1994; Wilgenbus and Majewski, 1994; Van Wymersch et al, 1996; Cursiefen et al, 2000; Davis and Samarakkody, 2002; Mengshol and Ornovold, 2003]. …”
Section: Resultsmentioning
confidence: 99%